Object-Oriented Representation of Environmental Phenomena: Is Everything Best Represented as an Object? - Bian, Ling (Annals of the Association of American Geographers, 2007)
A geographic space must be partitioned into a finite number of discrete pieces, such as points, lines, polygons, and grid cells, to accommodate the finite computing environment. Because these discrete geometric primitives can be implemented as software objects, the object-oriented computing paradigm might have encouraged the tendency to “objectify” spatial phenomena, regardless of whether they are best represented as objects. A critical review is necessary to assess whether object-orientation, a concept first developed outside geography, is suitable for spatial representation. This article reviews object-oriented spatial representation in the context of environmental modeling. The review is organized into four topics: (1) the principles underlying object-orientation, (2) the categorization of environmental phenomena, (3) GIS data models and their object-oriented implementation, and (4) the compatibility between these three sets of concepts. The discussion argues that spatial objects, regions, and fields represent three categories of phenomena that are well represented, reasonably represented, and not well represented by the objects, respectively. Reprinted by permission of the publisher.